2015
DOI: 10.1111/hae.12704
|View full text |Cite
|
Sign up to set email alerts
|

Open synovectomy of the ankle joint in young haemophiliacs: mid‐term to long‐ term results of a single‐centre series of 32 procedures

Abstract: Our long-term results support that clinical scores are improved even if radiological scores progress. Open synovectomy retards the progression of the arthropathy, but not stops it. Bleeding and pain are controlled and even if recurrence of bleedings is frequent, it is less severe, less painful and requiring less factors replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…For example, in Italy the median life expectancy of haemophiliacs increased from 62 years between 1990 and 1999 to 71 years during 2000–2007 . Early surgical intervention is also important in young haemophiliacs for slowing disease progression and preventing lasting joint damage . Individuals with severe haemophilia A (FVIII <1% of normal) require intensified FVIII replacement during surgery, as well as during the immediate postoperative recovery period until wound healing is complete (>10 days in major surgery) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Italy the median life expectancy of haemophiliacs increased from 62 years between 1990 and 1999 to 71 years during 2000–2007 . Early surgical intervention is also important in young haemophiliacs for slowing disease progression and preventing lasting joint damage . Individuals with severe haemophilia A (FVIII <1% of normal) require intensified FVIII replacement during surgery, as well as during the immediate postoperative recovery period until wound healing is complete (>10 days in major surgery) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the use of open synovectomy for haemophilic ankle arthropathy; however, only a small number of patients were investigated . Greene reported the results of open synovectomy in five patients with severe haemophilic ankle arthropathy over a mean follow‐up of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Pantopoulos et al reported a study involving six patients with a mean age of 29.6 years (range 8‐51 years) who underwent open synovectomy and a 32‐month follow‐up (range 12‐84 months). Mingo‐Robinet et al reported a study involving 21 patients aged <18 years with haemophilic ankle arthropathy with a mean follow‐up of 15.4 years. These reports show that open synovectomy was essentially restricted to the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of intraarticular ankle bleedings requiring transfusion was reduced from an average of 3.4 per month (range, 0.3-5 per month) for the 6 months before the synovectomy to 0.1 per month (range, 0-0.2 per month) for the 12 months prior to the latest follow-up [38]. Mingo-Robinet et al [39] performed 32 open synovectomies in 21 patients with haemophilia with a mean age of 7.8 years. The mean follow-up in this study was 15.4 years, ranging from 5 to 26.2 years.…”
Section: Arthroscopic Debridementmentioning
confidence: 97%